Messages of Race and Sexuality in Octavia E. Butler’s Fledgling - Borders, Maggie (My University, 2019)
In her final novel, Fledgling, Octavia E. Butler examines race, sexuality, and desire in a vampire novel that is radically different from others in that literary genre. Fledgling’s protagonist Shori, a young Black vampire, physically appears to be in her early teens. The novel begins with Shori waking up from a violent and traumatic attack that removed her memory of her vampire family or people, called Ina. The Ina have very different romantic relationships than traditional humans do. Several scholars have explored different aspects of Fledging. Kristen Lillvis examines Fledgling in relation to social issues, Mildred Mickle discusses its connection to addictions, and Gregory Hampton examines how race and gender politics affect the heroines of both Fledgling and Parable of the Sower. Fledgling may appear to be a simple fantasy or science fiction novel, but it is also a comment on Black female sexuality.